Everolimus in Invasive Malignant Renal Epithelioid Angiomyolipoma - Guo, Gang; Gu, Liangyou; Zhang, Xu (Frontiers in Oncology, 2021)
Background: To evaluate the efficacy and safety of everolimus, a mTOR inhibitor, on invasive malignant renal epithelioid angiomyolipoma (EAML). Materials and Methods： From Oct 2014 to May 2019, we collected data from 7 patients with a definite (clinical and pathological) diagnosis of EAML received everolimus in our hospital. Targeted sequence capture array technique with next-generation of high throughput sequencing (NGS) were performed to detect mutations of TSC1/2 genes. All patients had received surgery and everolimus. The clinical efficacy and safety of the therapy were evaluated. Results: Mutations of TSC1 and TSC2 were detected in 2 and 3 patients though targeted sequence capture array technique with NGS, respectively. Among 7 patients, 3 had missense mutations, 1 had nonsense mutation, and 1 had the large fragment deletion mutation. Five patients accompanied with tuberous sclerosis complex (TSC) were identified. All patients were administered 10mg everolimus once daily, the treatment duration lasted for 3 to 28 months. The objective response was assessed 3 months later, 5 partial response, 2 stable disease (SD), the mean greatest tumor diameter of all patients decreased from 9.6cm to 5.2cm. Six patients stayed SD and 1 patient died during follow up. Patients accompanying with TSC had better responses to everolimus compared with non-TSC. Conclusion: The mTOR inhibitor can be an effective treatment for patients with invasive malignant renal EAML. Patients with TSC may benefit more from the therapy.